Effect of dietary manganese and zinc levels on growth and bone status of Senegalese Sole (Solea senegalensis) Post-Larvae - Viegas, Michael N. (2020)
Essential dietary trace elements, such as zinc (Zn) and manganese (Mn), critically influence a wide range of physiological, metabolic, and hormonal processes in fish larvae and post-larvae. Despite their importance for normal fish growth and skeletal development, trace mineral nutrition has not been extensively studied in the early stages of development of fish. Post-larvae of an emergent aquaculture species, Senegalese sole (Solea senegalensis), were the subject of this study in order to better understand the effects of diet supplementation of trace minerals upon fish larval development and performance. Sole post-larvae were fed a combination of organic Mn (45 and 90 mg kg-1 feed) and organic Zn (100 and 130 mg kg-1 feed) and survival, growth, mineral deposition rates, and vertebral bone status were assessed. Our results showed that although no significant effect was found on the growth performance of Senegalese sole post-larvae, Mn and Zn supplementation to a commercial microdiet for marine fish larvae at higher dietary levels (Mn at 90 mg kg-1 and Zn at 130 mg kg-1) improved larval survival, decreased the severity of vertebral malformations, and increased the deposition of Mn in bone.